Power, Truth, Struggle and Risk: The Ethical-Political Perspectives of Nietzsche and Foucault - Zengotita, Alonso (Foro Interno, 2016)
The ethical and political views expressed by Foucault on cura sui (self-concern), which involve the practice of parrhesia, have been criticized as being a purely solipsistic act that only seeks to resist power from an aesthetic and individual disposition. Starting with the Foucauldian notion of parrhesia, which resembles the way Nietzsche conceived truth as risk-based, this work aims to point out two issues: the first is that this resemblance arises from a comparison of the concepts of power relations in Foucault and of struggle in Nietzsche, which in turn, allow a wider conception of cura sui; the second is that the differences in the understanding of these power and struggle relations can be brought together from what is respectively antagonistic in both ethical and political terms, i.e., Foucault’s view of power as domination in contrast with Nietzsche’s view of power as a civilization inheriting Christian values.